Catheter ablation of the parahisian accessory pathways from the aortic cusps—Experience of 20 cases—Improving the mapping strategy for better results. (22nd April 2020) - Chokr, Muhieddine O.; de Moura, Lucas G.; Aiello, Vera D.; dos Santos Sousa, Ítalo B.; Lopes, Hugo B.; do Carmo, Andre A. L.; Pisani, Cristiano F.; Hardy, Carina A.; de Melo, Sissy L.; Scanavacca, Mauricio I.
Abstract: Introduction: Catheter ablation of the parahisian accessory pathways (PHAP) has been established as the definitive therapy for this type of arrhythmia. However, the PHAP proximity to the normal atrioventricular conduction system makes the procedure technically challenging. Here, we have reported a case series of 20 patients with PHAP who underwent aortic access ablation to evaluate the safety and efficacy of this approach in the PHAP ablation. Methods and Results: The ablation through the aortic cusps was the successful approach in 13 of 20 (65%) of the cases. In 11 patients, the aortic approach was the initial strategy for ablation, and the accessory pathway was eliminated in seven (63.6%) of them. The aortic approach followed a failed right‐sided attempt in nine patients. In six (66.7%) patients, the ablation was successful with the aortic approach. The only independent predictor for the successful ablation with each approach was the earliest ventricular activation before delta wave (predelta time) and a right‐sided earliest ventricular activation of more than 23 ms had high sensitivity and specificity for right‐sided success. Systematically using the two strategies (right and left approaches), the ablation of the PHAP was successful in 18 (90%) patients. Conclusion: The aortic approach seems to be a safe and effective strategy for the ablation of PHAP. It can be used when the right‐sided approach fails or even considered as an initial strategy when the predelta time is less than 23 ms in the right septal region. When combining the right‐ and left‐sided approaches, the success rate is high. We believe that the retrograde aortic approach remains a key tool for this challenging ablation.